2018
DOI: 10.1007/s11882-018-0781-y
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Allergic Rhinitis as a Strategy for Preventing Asthma

Abstract: AR is frequently associated with asthma, leading to the concept that these two conditions are different aspects of the same disease. There is increasing evidence that AR precedes the onset of asthmatic symptoms and current treatment strategies are beneficial in symptom control with no impact prevention. There is limited knowledge about the risk factors responsible for the progression of AR to asthma, though recent data supports the notion that it is possible to prevent asthma onset by allergen immunotherapy. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 89 publications
1
21
0
6
Order By: Relevance
“…Furthermore, our findings also revealed that in 2011, as for 2015, the association between age and epidemiological pattern complexity is confirmed, as already discussed in literature [ 31 , 32 ]. Therefore, both for 2011 and 2015, among adults until 65 years, all the patterns appeared more complex than other age groups.…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, our findings also revealed that in 2011, as for 2015, the association between age and epidemiological pattern complexity is confirmed, as already discussed in literature [ 31 , 32 ]. Therefore, both for 2011 and 2015, among adults until 65 years, all the patterns appeared more complex than other age groups.…”
Section: Discussionsupporting
confidence: 89%
“…Allergic asthma is a chronic inflammatory airway disease characterized by airway remodeling, hyperreactivity and short of breath (Morjaria et al, 2018). Currently, three main prescriptions are used to treat asthma patients, which include inhaled short-acting and long-acting β2 agonists, inhaled and oral corticosteroids, and leukotrienes agonists (Gibeon and Menzies-Gow, 2013; Telia et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Three years later, there was a significant reduction in asthma symptoms in the groups treated with immunotherapy, together with a marked improvement in rhinitis symptoms. In their review, Morjaria et al ( 301 ) concluded that, unlike corticosteroids and other symptomatic treatments, immunotherapy prevented development of other allergic conditions in individuals at risk.…”
Section: Diagnosis Of Allergic Rhinitismentioning
confidence: 99%